Building Trust in Hyperconnected World: New Media, Public Relations, and Public Policy - Onrak, Methaporn; Phuengpha , Noppawan (Procedia of Social Sciences and Humanities, 2024)
In today's hyperconnected world, building trust in public relations and public policy has become increasingly crucial. With the rapid expansion of the internet and social media, organizations and governments must navigate a complex environment to establish and maintain trust among the public. The transparency and credibility of communication, particularly through digital media, are essential for fostering relationships with citizens. This paper examines the role of new media in shaping public relations and public policy, highlighting the importance of trust-building factors such as transparent communication, accuracy, and sincerity.Through a quantitative approach, the study explores the dynamics between public trust and the use of digital platforms in conveying policy-related information. By analyzing public engagement and perception metrics from social media platforms, websites, and other digital communication tools, the research provides insights into how trust is developed and maintained in this new media landscape.The findings suggest that leaders who embrace authenticity and transparency in their communication strategies, such as Canadian Prime Minister Justin Trudeau are more successful in gaining public trust. Moreover, the study indicates that public participation in policy discussions via digital media significantly enhances trust levels, particularly when accurate and verified information is disseminated. This paper emphasizes the need for policymakers and public relations professionals to adapt to the digital age by integrating trustworthy communication practices into their strategies.